Influence of Planting Materials and Land tenure system on Mango Production in Endo Ward, Elgeyo Marakwet County, Kenya - Kipchumba , Abraham; Odwori, Paul O.; Kebeney , Syphyline (African Journal of Education,Science and Technology (AJEST), 2023)
Mango (Mangifera indica L.) is Kenya’s third most important fruit in terms of acreage and total production. Mango is grown in Coastal, Eastern, and Central and in Rift valley dominantly in Kerio Valley belt due to favourable environmental conditions. Recent research, however, has reported a decline in mango production in Endo Ward. Therefore, the objective of this study was to determine the factors that affect smallholder mango production in Endo Ward, Elgeyo Marakwet County. A survey was carried out in which a sample population of 281 farmers were chosen from a target population of 937 farmers. A simple random sampling technique was used in selecting the locations and the respondents. Primary data was obtained using questionnaires and interview on key informants. Data collected was analysed using descriptive and inferential statistics. The results indicated that 42.96% of planting materials are obtained by farmers from local private nurseries while 23.47% get from Kerio Valley Development Authority (KVDA) nurseries. Thus, the high cost deterred some farmers from accessing mango planting materials easily hence decline in production. Results also showed that the land tenure system was such that 89.53% of the farmers owned land communally while only 10.47 % owned individual land. This lack of property rights on Land resource did not motivate farmers sufficiently enough to invest optimally in mango production. This study recommends that there is need to assist the farmers to access affordably planting materials and grant tittle deeds to farmers to motivate optimum individual effort.